Automatic handling of shade net and irrigation in greenhouse with tomatoes (Scientia Agropecuaria, 2011)
Greenhouse vegetable production in México and worldwide has become important. Following greenhouses automation, a simple controller was designed to open and close shading nets to reduce incident radiation and excessive evapotranspiration. Irrigation period were radiation controlled and did not turn on the pump with clouds or moon radiation, saving 35% of water. The nets remained closed during the night and were opened during scarce radiation. In the tomato greenhouse experiment, every three months analysis was carried on manual and automatic net control. Maximum incident radiation was achieved in May and August when no shading nets were used. Air temperature increased to 28°C in August decreasing by 50% fruit size. Fruit temperature decreased 2.5°C when nets were used decreasing tomato cracking.
Keywords: Irrigation management; greenhouse; shading management; radiation; tomato weight; photo-cell.